Positive Solutions of nth-Order Boundary Value Problems with Integral Boundary Conditions - Karaca, Ilkay Yaslan; Fen, Fatma Tokmak (Mathematical Modelling and Analysis, 2015)
In this paper, by using double fixed point theorem and a new fixed point theorem, some sufficient conditions for the existence of at least two and at least three positive solutions of an nth-order boundary value problem with integral boundary conditions are established, respectively. We also give two examples to illustrate our main results.